ANALISIS KUALITAS SELADA (Lactuca sativa L.) YANG DITANAM PADA DUA MEDIA SELAMA PENYIMPANAN DINGIN - Rantung, Livia E.; Lengkey, Lady C. Ch. E.; Wenur, Frans (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
ABSTRACTThe objective of this study was to investigate the quality (weight, color, stem firmness and total dissolved solids) of hydroponic and soil culture lettuce (Lactuca sativa L.). This study used a non factorial completely randomized design with two treatments (type of planting media) as follows hydroponic lettuce and soil culture lettuce. This research conducted 9 replications. Data were analyze with ANOVA to determine whether there is a difference in the quality of lettuce after storage at cold temperatures. Lettuce is packed and placed at cold storage of 50C. The change in weight, color, stem firmness and total dissolved solids were observed every 3 days during storage period. The result of this study show that hydroponic lettuce and soil lettuce gave different responses during cold storage. After 15 days of storage, soil culture lettuce has better quality than hydroponic lettuce in terms of maintaning the weight and total dissolved solids. While, in maintaning the color and firmness of the stem, hydroponic lettuce has better quality. Keywords: Lettuce, planting media, cold storage